2011
DOI: 10.1111/j.1365-2966.2011.18648.x
|View full text |Cite
|
Sign up to set email alerts
|

Is GeV emission from Gamma-Ray Bursts of external shock origin?

Abstract: Recent observations of Gamma‐Ray Bursts (GRBs) by the Fermi Large Area Telescope (LAT) revealed a power‐law decay feature of the high‐energy emission (above 100 MeV), which led to the suggestion that it originates from an external shock. We analyse four GRBs (080916C, 090510, 090902B and 090926A) jointly detected by Fermi LAT and Gamma‐ray Burst Monitor (GBM), which have high‐quality light curves in both instrument energy bands. Using the MeV prompt emission (GBM) data, we can record the energy output from the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…The LAT high-energy extended emission typically decreases as a function of time Ackermann et al 2013), which supports the external forward shock model. Furthermore, the detailed spectral and temporal properties are consistent with those predicted by the external shock model (Kumar & Barniol Duran 2009De Pasquale et al 2010;Ghisellini et al 2010;Panaitescu 2017), although bright and spiky temporal structures observed in the prompt phase of LAT light curves challenge this interpretation Maxham et al 2011). Recently, Gompertz et al (2018) applied the closure relation to a large sample of LAT-detected long GRBs and identified their surrounding environment conditions.…”
Section: Introductionmentioning
confidence: 68%
“…The LAT high-energy extended emission typically decreases as a function of time Ackermann et al 2013), which supports the external forward shock model. Furthermore, the detailed spectral and temporal properties are consistent with those predicted by the external shock model (Kumar & Barniol Duran 2009De Pasquale et al 2010;Ghisellini et al 2010;Panaitescu 2017), although bright and spiky temporal structures observed in the prompt phase of LAT light curves challenge this interpretation Maxham et al 2011). Recently, Gompertz et al (2018) applied the closure relation to a large sample of LAT-detected long GRBs and identified their surrounding environment conditions.…”
Section: Introductionmentioning
confidence: 68%
“…After the GBM-band burst is over, LAT-band photons are usually observed to decay with a single power law with a slope ∼ −1.4 [319,155]. This suggests either that the entire high energy emission has a different origin from the MeV emission (which is in contrast with the points 2 and 6 above) [322,323,319], or that the high energy lightcurve is the superposition of two components with a second (external shock) component setting in as the prompt emission fades [155,320].…”
Section: Origin Of High Energy Emissionmentioning
confidence: 98%
“…This requires some extreme parameters for the external shock [322,323], a radiative blastwave [319] or a Klein-Nishina cooling dominated shock [325,326]. GeV emission during the prompt emission phase, however, is not easy to interpret within the external shock model [327,328,320], and is likely of an internal origin, as suggested by the data [155]. (3) The delayed onset of GeV emission has been interpreted as emergence of the upscattered cocoon emission [324], synchrotron emission from shock accelerated protons [249], delayed residual internal shock emission [329], as well as the delayed fireball acceleration to an extremely high Lorentz factor [330].…”
Section: Origin Of High Energy Emissionmentioning
confidence: 99%
“…As successful descriptions of optical light curves, they found values of microphysical parameters similar to those obtained in this work, indicating that the jet was magnetized. Using the MeV prompt emission (GBM) data and assuming a constant radiative efficiency, Maxham et al (2011) were able to track the energy accumulation in the external shock with an internal/external shell model code. Authors analyzed some LAT bursts (including GRB 090510) and suggested that the high-energy emission present in most of LAT burst during the prompt phase is most likely a superposition of a gradually enhancing external shock component and a dominant emission component that is of an internal origin.…”
Section: Discussionmentioning
confidence: 99%